MEMPREDIKSI JUMLAH PENERIMAAN DAN PERMINTAAN DARAH DI PALANG MERAH INDONESIA (PMI) KITA MEDAN DENGAN MENGGUNAKAN METODE ID3 (STUDI KASUS: PMI KOTA MEDAN) - Sirait, Annisa Corry Nauli; Buulolo, Efori; Hutabarat, Hukendik (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The Indonesian Red Cross (PMI) is a national association organization in Indonesia engaged in the field of social humanity. In certain months the blood demand has increased dramatically, this causes the availability of blood in the Indonesian Red Cross Medan City increasingly thinning. In addition to lack of blood, excess blood supply is also common in the Indonesian Red Cross. To overcome the above problems, the Indonesian Red Cross (PMI) of Medan City is supplying blood stock so that when the needs are high they can balance the stock and if their blood needs are low they can stabilize the blood so that the blood is not wasted. To overcome these problems, it is necessary to build an application for the Implementation of the Amount of Blood Receipts and Demand in the Medan Red Cross by using the ID3 (Iterative Dichoimoiser 3) method so that it helps in the process of equalizing blood to make it more accurate and the decisions determined to be valid and satisfactory.Keywords: Data Mining, Blood Acceptance and Demand, Id3 (Iterative Dichoiomiser)